Greenhouse Gas Emissions From Biofilters for Composting Exhaust Ammonia Removal - Shang, Bin; Zhou, Tanlong; Tao, Xiuping; Chen, Yongxing (Frontiers in Bioengineering and Biotechnology, 2022)
Emissions of odorous compounds, such as ammonia (NH3)from composting have negative agronomic and environmental impacts. Biofilter is widely used for NH3 removal, with one of its potential detrimental by-products being nitrous oxide (N2O), which is a higher warming potential greenhouse gas (GHG). The aim of the study was to evaluate the effect of empty bed retention time (EBRT) on GHG emissions from biofilters for removing NH3 from composting. Composting experimental trials lasted 6 weeks, and composting materials were mixtures of dead pigs and manure. Three groups of biofilters with 1.2 m-height, 0.3 m-inner diameter and 1.0 m media depth were conducted with EBRT of 30s, 60s and 100s, respectively. Each treatment was done in triplicate, and the gas was monitored using the dynamic emission vessel method. The Spearman’s correlation analysis showed a significantly positive correlation between inlet concentrations (ICs) of NH3 and increased N2O concentrations: =0.707, 0.762, and 0.607 with P≤0.0001 for biofilters with EBRT of 30s, 60s and 100s, respectively. The fraction of NH3-N denitrified into N2O-N in biofilters with EBRT of 60s and 100s were higher than that with EBRT of 30s. The total global warming potential (GWP) increased by 126%, 162% and 144% for biofilters with EBRT of 30s, 60s and 100s, respectively. These results indicate that biofilters with longer EBRT will lead to higher GWP production. Future research on odorous mitigation for composting with biofilter should focus more on greenhouse gas emissions.